PENERAPAN METODE BUZZ GROUP UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) DI KELAS XI IPA SMA N 1 RENGAT - Yulita Sari; Islamias '; Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Research on the application of metodh Buzz Group has been conducted to determine the increase in student achievement on the subject of solubility and solubility product (Ksp) in class XI Science SMAN 1 Rengat. Form of research is experimental research with pretest-posttest design.. The research was conducted on the even semester in academic year 2013/2014. The sample consisted of two classes, namely class XI IPA1 as the experimental class and the class as a class XI IPA2 controls randomly selected after tests of normality and homogeneity test. Experimental class is a class that is treated by applying a metodh of Buzz Group, while the control class was treated to a lecture. Data analysis technique used is the t-test. Based on analysis of data obtained t > ttable ie 2,34 > 1,67, means that the application of metodh Buzz Group can improve student achievement on the subject of solubility and solubility product (Ksp) in class XI Science SMAN 1 Rengat. Large increase in the application of methods buzz group on the subject of solubility and solubility product in the experimental class is 8.13%.Keywords: Metodh of Buzz Group, Learning Achievement, Solubility and solubility product